Portrayal of Hallucination in Coraline Graphic Novel - Yan Ardian Subhan; Devinta Cicilia Agustin; Devyna Nurlaelaningrum; Naesya Feani; Suci Ardanisa (LPPM Universitas Bina Sarana Informatika, 2023)
The purpose of this study is to analyze the Hallucinations issue in the Graphic Novel Caroline. The condition when someone who experiences sees, hears, feels, smells and tastes things that are not real is Hallucinations. Many things can cause hallucinations. One of them is a very strong desire to get something. The graphic novel Coraline has abundant evidence of the hallucinations experienced by the main character. Freud (1953) felt that hallucinations were very much like dreams and that both conditions represented a psychotic state in which there is no sense of time at all. Coraline always enters a parallel world when she sleeps and sees her parents in different forms and traits. The analysis is used psychological approach especially Sigmund Freud's Psychoanalytic theory. The psychological approach can be used to analyze the characters in a work. The main character and her hallucinations are important for analysis. The focus of this study is to find confirmation of Id, Ego, and Super Ego from Coraline's hallucinations. The method used is qualitative in analyzing graphic novels